2004
DOI: 10.1001/archinte.164.1.83
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehensive Care Team

Abstract: Consultation by a palliative medicine team led to improved patient outcomes in dyspnea, anxiety, and spiritual well-being, but failed to improve pain or depression. Palliative care for seriously ill outpatients can be effective, but barriers to implementation must be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
127
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 418 publications
(129 citation statements)
references
References 47 publications
1
127
1
Order By: Relevance
“…8 The Project ENABLE II randomized trial found that a nurse-led concurrent palliative care intervention improved the QOL and mood of patients with advanced gastrointestinal, lung, genitourinary, or breast cancer. 9 Several other palliative care trials published over the last 10 years observed better patient satisfaction, 10,11 improved QOL in family caregivers, 12 improved symptom relief, 13 and lower health care costs. 10,11 The American Society of Clinical Oncology (ASCO) issued a Provisional Clinical Opinion with recommendations that all cancer patients with metastatic disease and/or high symptom burden be given concurrent palliative and oncology care.…”
Section: Introductionmentioning
confidence: 95%
“…8 The Project ENABLE II randomized trial found that a nurse-led concurrent palliative care intervention improved the QOL and mood of patients with advanced gastrointestinal, lung, genitourinary, or breast cancer. 9 Several other palliative care trials published over the last 10 years observed better patient satisfaction, 10,11 improved QOL in family caregivers, 12 improved symptom relief, 13 and lower health care costs. 10,11 The American Society of Clinical Oncology (ASCO) issued a Provisional Clinical Opinion with recommendations that all cancer patients with metastatic disease and/or high symptom burden be given concurrent palliative and oncology care.…”
Section: Introductionmentioning
confidence: 95%
“…Integrating palliative care early in the course of treatment for patients with terminal cancer has gained attention in recent years as a promising strategy for improving patients’ quality of life (QOL)[1,2] and extending their survival. [3] In addition, early palliative care has been linked with measures of less aggressive end-of-life care.…”
Section: Introductionmentioning
confidence: 99%
“…While traditional approaches to symptomatic distress often focus primarily on the management of physical symptoms, this study’s findings add to a growing body of literature suggesting that different forms of distress are often interconnected, co-occurring, and relevant to the overall health outcomes of older adults. 5,7,8, 9,20 …”
Section: Discussionmentioning
confidence: 99%
“…For example, physical symptoms are independently associated with worsening quality of life, future functional impairment, patient dissatisfaction, and increased healthcare costs via greater primary care and urgent care visits. 7,8 Psychological and social symptoms also contribute to worse physical distress and poorer health outcomes. 9,10 And a growing body of evidence suggests that existential suffering, which adversely affects quality of life and overall well-being, may also contribute to worse physical health among the seriously ill, though the literature exploring the link between existential distress and physical health outcomes is still in its early stages.…”
Section: Introductionmentioning
confidence: 99%